Philippe Denys. : Objets d'Art from Europe 1880-1950. - Philippe Denys, Bruxelles; Denys, Philippe (Brussel : Philippe Denys, 2001)
Alef, Thorwald ; Andersen, Just ; Bellotto, Umberto ; Bloch, Kresten ; Bonome, Santiago-Rodriguez ; Borsani, Gaetani ; C.G. Hallbergs Guldsmeds AB ; Czeschka, Carl Otto ; Dixon, James ; Fontana, Lucio ; Fontana Arte ; Gariboldi, Giovanni ; Halier, Carl ; Hansen, Karl Gustav ; Höglund, Erik ; Koppel, Henning ; Lafon, Paul Dupre ; Magnus, Elmquist Hugo Carl ; Michelucci, Giovanni ; Nordstrom, Patrick ; Prutscher, Otto ; Puiforcat, Jean ; Quistgaard, Jens H. ; Salto, Axel ; Sarpaneva, Timo ; Souche-Lappara ; Strömgren, Axel ; Tetard ; Thorsson, Nils ; Utzon-Frank, Einar ; Wirkkala, Tapio ; Wolfers, Marcel ; Wretling, Otto
Objets d'Art from Europe 1880-1950, Philippe Denys, Bruxelles, Novembre 2001
Engels
Frans
boek